2019
DOI: 10.1139/cjfas-2018-0041
|View full text |Cite
|
Sign up to set email alerts
|

Examining the potential of otolith chemistry to determine natal origins of wild Lake Michigan Chinook salmon

Abstract: Previous research has demonstrated a large movement of hatchery-reared Chinook salmon (Oncorhynchus tshawytscha) from Lake Huron to Lake Michigan, suggesting the potential for wild fish to exhibit similar movement patterns. We assessed the feasibility of using otolith microchemistry to estimate the natal source composition of wild Chinook salmon in Lake Michigan and evaluate interbasin movement. Otolith pairs were extracted from juvenile and adult fish collected in 2015 and 2016 from Great Lakes tributaries. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Though we failed to identify highly similar published applications to our own, in which phenotypic traits were used to assign adult Chinook Salmon to genetic lineage, analogous studies showed similar or reduced classification success. Researchers correctly assigned between 74.2% and 87.8% of adult Chinook Salmon to natal Great Lakes basins using otolith microchemistry (Maguffee et al 2019) and 75% and 68% of female and male adult Chinook Salmon, respectively, to the appropriate hatchery status using morphometrics (Busack et al 2007). Harvey et al (2014) attempted to assign juvenile Chinook Salmon to stock, delineated by run timing, using length-at-date data with mixed success; group-specific classification success varied between 1.9% and 75%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though we failed to identify highly similar published applications to our own, in which phenotypic traits were used to assign adult Chinook Salmon to genetic lineage, analogous studies showed similar or reduced classification success. Researchers correctly assigned between 74.2% and 87.8% of adult Chinook Salmon to natal Great Lakes basins using otolith microchemistry (Maguffee et al 2019) and 75% and 68% of female and male adult Chinook Salmon, respectively, to the appropriate hatchery status using morphometrics (Busack et al 2007). Harvey et al (2014) attempted to assign juvenile Chinook Salmon to stock, delineated by run timing, using length-at-date data with mixed success; group-specific classification success varied between 1.9% and 75%.…”
Section: Discussionmentioning
confidence: 99%
“…Classification using random forests.-We used random forests to classify fish to genetic lineage, using observed phenotypic traits, based on their proven predictive performance relative to similar classification procedures (Breiman 2001; Maguffee et al 2019;Smolinski et al 2020). We restricted fish inclusion to only those assigned to a tule or upriver bright reporting group; all other groups were either identified readily using unique fin clip markings or were rare among sampled fish.…”
Section: Methodsmentioning
confidence: 99%
“…Stable isotope analysis may provide a solution to identify the early origin of adults caught in the Scottish rivers and has been successfully used in a number of salmonid species to identify natal origins (e.g., Barnett-Johnson et al, 2008;Brennan et al, 2015;Gao & Bean, 2008;Hanson et al, 2013;Maguffee et al, 2019;Smith et al, 2006). It might be expected that the very different river and early smolt marine environmental conditions in the White Sea/Northern Barents Sea/Northern Atlantic compared to the North Sea and/or more southerly areas of the eastern Atlantic may result in different stable isotope ratios in early rings of pink salmon otoliths from the different areas.…”
Section: Discussionmentioning
confidence: 99%
“…Such properties have contributed to the application of otolith chemistry in the determination of fish natal origin (Schaeffer et al 2014;Lazartigues et al 2016;Maguffee et al 2019), migratory behaviour (Secor et al 1995;Elsdon and Gillanders 2003a;Morissette et al 2016) and population structure (Tanner et al 2016;Spurgeon et al 2018;Wright et al 2018). We consider that such applications could be helpful in invasion biology but remain to be widely adopted.…”
Section: Introductionmentioning
confidence: 99%